Relation between the Atmospheric Boundary Layer and Impact Factors under Severe Surface Thermal Conditions - Yinhuan Ao; Jiangang Li; Zhaoguo Li; Shihua Lyu; Cailian Jiang; Minzhong Wang (Advances in Meteorology)
This paper reported a comprehensive analysis on the diurnal variation of the Atmospheric Boundary Layer (ABL) in summer of Badain Jaran Desert and discussed deeply the effect of surface thermal to ABL, including the Difference in Surface-Air Temperature (DSAT), net radiation, and sensible heat, based on limited GPS radiosonde and surface observation data during two intense observation periods of experiments. The results showed that (1) affected by topography of the Tibetan Plateau, the climate provided favorable external conditions for the development of Convective Boundary Layer (CBL), (2) deep CBL showed a diurnal variation of three- to five-layer structure in clear days and five-layer ABL structure often occurred about sunset or sunrise, (3) the diurnal variation of DSAT influenced thickness of ABL through changes of turbulent heat flux, (4) integral value of sensible heat which rapidly converted by surface net radiation had a significant influence on the growth of CBL throughout daytime. The cumulative effect of thick RML dominated the role after CBL got through SBL in the development stage, especially in late summer, and (5) the development of CBL was promoted and accelerated by the variation of wind field and distribution of warm advection in high and low altitude.